Recent advancements in oral administration of insulin-loaded liposomal drug delivery systems for diabetes mellitus - Wong, Chun Yuen; Al-Salami, Hani; Dass, Crispin (Elsevier BV, 2018)
© 2018 Elsevier B.V. Diabetes is a chronic medical condition, which is characterised by high blood sugar level. Exogenous insulin is commonly administered subcutaneously for the management of diabetes. However, daily injections of insulin could result in poor patient compliance and various side-effects. Although oral administration offers benefits, insulin is vulnerable to enzymatic degradation, chemical instability and poor gastrointestinal absorption. There is an absence of reviews on insulin-loaded liposomal drug carriers, despite that fact that liposomes have gained considerable attention recently for oral delivery of insulin. They demonstrate favourable characteristics, such as versatility, biocompatibility, protective effect against enzymatic degradation, and cell-specific targeting. In this review, we will explore the status quo for oral delivery of insulin-loaded liposomal formulations, followed by discussing the state of art of these vesicles. This review will provide a detailed overview on insulin-loaded conventional liposomes, and 7 types of current novel formulations. Lastly, the future direction for oral bioavailability enhancement and development of such nanoscale drug delivery systems will be discussed. Further optimisation in the drug entrapment efficiency and gastrointestinal absorption will be required to develop a clinically successful oral liposome-insulin formulation.